Sei sulla pagina 1di 3

2018 MTAP-DepEd Program of Excellence in Mathematics Grade 11 Session 1 TG

I. Explain the definition of function briefly and when is a given function or not a function
1. function
2. function(rational)
3. function
4. function
5. function(piecewise)
6. function
7. function
8. not a function
9. function (you will not find a value of x that will have 2 values for y
10. function (domain is restricted to union of even and odd integers)
11. not a function if you let x=2 you will have 2 values
12. function x = 2 will only have 1 value
13. function
14. function
15. not a function
16. function (a point is a function with only one domain and one range)
17. not a function
18. function(step-function)
19. function

II. Perform the indicated operation given that f(x) = x + 2, g(x) = √𝑥, h(x) = x2-4

1. x + 2 + √𝑥 10. √𝑥 + 2
2. √𝑥 − 𝑥 2 + 4 11. 18, they can use the answer in
3. x√𝑥+2√𝑥 number 6 to solve this, any method
𝑥+2 𝑥√𝑥+2√𝑥 would do.
4. =
√𝑥 𝑥 12. 6, they can use answer in 7
5. √𝑥 2
−4 13. 24, they can use answer in 8
2
6. x + x- 2 14. 2, they can use answer in 9
7. x2 – x - 6 15. 4, they can use answer in 10
8. 𝑥 2 √𝑥 − 4√𝑥
𝑥 2 −4
9. = 𝑥 − 2, 𝑥 ≠ −2
𝑥+2

III. Perform the indicated operation.


1 2 𝑥−2 2𝑥 3𝑥−2
1. + 𝑥−2 = 𝑥(𝑥−2) + 𝑥(𝑥−2) = 𝑥 2 −2𝑥
𝑥
1 2 𝑥−2 2𝑥 −𝑥−2
2. − 𝑥−2 = 𝑥(𝑥−2) − 𝑥(𝑥−2) = 𝑥 2 −2𝑥
𝑥
1 2 2 2
3. ( ) = 𝑥(𝑥−2) = 𝑥 2 −2𝑥
𝑥 𝑥−2
1
𝑥 1 𝑥−2 𝑥−2
4. 2 = (𝑥 ) ( )=
2 2𝑥
𝑥−2
𝑥 2 −1 𝑥 2 −3𝑥+2 (𝑥+1)(𝑥−1) (𝑥−1)(𝑥−2) ((𝑥+1)2 (𝑥−1)+(𝑥−1)(𝑥−2)2 )
5. + 𝑥 2 +3𝑥+2 = (𝑥+2)(𝑥−2) + (𝑥+1)(𝑥+2) = =
𝑥 2 −4 (𝑥−2)(𝑥+1)(𝑥+2)
(𝑥 3 +𝑥 2 −𝑥−1)+(𝑥 3 −5𝑥 2 +8𝑥−4) 2𝑥 3 −4𝑥 2 +7𝑥−5
=
𝑥 3 +𝑥 2 −4𝑥−4 𝑥 3 +𝑥 2 −4𝑥−4
𝑥 2 −1 𝑥 2 −3𝑥+2 (𝑥+1)(𝑥−1) (𝑥−1)(𝑥−2) ((𝑥+1)2 (𝑥−1)−(𝑥−1)(𝑥−2)2 )
6. 𝑥 2 −4 − 𝑥 2 +3𝑥+2 = (𝑥+2)(𝑥−2) − (𝑥+1)(𝑥+2) = (𝑥−2)(𝑥+1)(𝑥+2)
=
(𝑥 3 +𝑥 2 −𝑥−1)−(𝑥 3 −5𝑥 2 +8𝑥−4) 6𝑥 2 −9𝑥+3
= 𝑥 3 +𝑥 2 −4𝑥−4
𝑥 3 +𝑥 2 −4𝑥−4
𝑥 2 −1 𝑥 2 −3𝑥+2 (𝑥+1)(𝑥−1) (𝑥−1)(𝑥−2) (𝑥−1)2 𝑥 2 −2𝑥+1
7. 𝑥 2 −4 (𝑥 2 +3𝑥+2) = ((𝑥+2)(𝑥−2)) ((𝑥+1)(𝑥+2)) = (𝑥+2)2 = 𝑥 2 +4𝑥+4
𝑥2 −1
𝑥2 −4 𝑥 2 −1 𝑥 2 +3𝑥+2 (𝑥+1)(𝑥−1) (𝑥+1)(𝑥+2) (𝑥+1)2 𝑥 2 +2𝑥+1
8. 𝑥2 −3𝑥+2
= 𝑥 2 −4 (𝑥 2 −3𝑥+2) = ((𝑥+2)(𝑥−2)) ((𝑥−1)(𝑥−2)) = (𝑥−2)2 = 𝑥 2 −4𝑥+4
𝑥2 +3𝑥+2
IV. Solve for the following equations.

𝑥 12
1. 𝑥−2 = 6 → 𝑥 = 6(𝑥 − 2), 𝑥 ≠ 2 → 𝑥 = 6𝑥 − 12, 𝑥 ≠ 2 → 5𝑥 = 12, 𝑥 ≠ 2 → 𝑥 = 5
𝑥 1 𝑥+1
2. + = 1 → 𝑥+2 = 1 → 𝑥 + 1 = 𝑥 + 2, 𝑥 ≠ −2 → 1 = 2 → 𝑁𝑜 𝑝𝑜𝑠𝑠𝑖𝑏𝑙𝑒 𝑟𝑒𝑎𝑙 𝑠𝑜𝑙𝑢𝑡𝑖𝑜𝑛
𝑥+2 𝑥+2
𝑥+1 8 3𝑥+15 𝑥+1 4 𝑥+5 𝑥+5 𝑥+5
3. 𝑥−3 + 2𝑥−6 = → 𝑥−3 + 𝑥−3 = 𝑥−3 → 𝑥−3 = 𝑥−3 → 0 = 0, 𝑥 ≠ 3 → 𝐴𝑙𝑙 𝑟𝑒𝑎𝑙 𝑛𝑢𝑚𝑏𝑒𝑟𝑠 𝑒𝑥𝑐𝑒𝑝𝑡 3
3𝑥−9
𝑥−2 𝑥−1
4. 𝑥−3 = 𝑥+5 → (𝑥 − 2)(𝑥 + 5) = (𝑥 − 1)(𝑥 − 3), 𝑥 ≠ 3, −5
13
→ 𝑥 2 + 3𝑥 − 10 = 𝑥 2 − 4𝑥 + 3, 𝑥 ≠ 3, −5 → 7𝑥 = 13, 𝑥 ≠ 3, −5 → 𝑥 =
7
3 𝑥−2 3 𝑥−2
5. 𝑥+5 = 𝑥 2 +6𝑥+5 → 𝑥+5 = (𝑥+1)(𝑥+5) → 3(𝑥 + 1) = (𝑥 − 2), 𝑥 ≠ −1, −5
5
→ 3𝑥 + 3 = 𝑥 − 2, 𝑥 ≠ −1, −5 → 2𝑥 = −5, 𝑥 ≠ −1, −5 → 𝑥 = −
2
𝑥 2 +𝑥−12 𝑥 2 −3𝑥+2 𝑥+1 (𝑥+4)(𝑥−3) (𝑥−2)(𝑥−1) 𝑥+1 𝑥−3 𝑥+1
6. (𝑥 2 +2𝑥−8) (𝑥 2 +4𝑥−5) = 𝑥+2 → ((𝑥+4)(𝑥−2)) ((𝑥+5)(𝑥−1)) = 𝑥+2 → 𝑥+5 = 𝑥+2 , 𝑥 ≠ −4,2,1
→ (𝑥 − 3)(𝑥 + 2) = (𝑥 + 1)(𝑥 + 5), 𝑥 ≠ −4,2,1 → 𝑥 2 − 𝑥 − 6 = 𝑥 2 + 6𝑥 + 5, 𝑥 ≠ −4,2,1
11
→ −7𝑥 = 11, 𝑥 ≠ −4,2,1 → 𝑥 = − , 𝑥 ≠ −4,2,1
7
𝑥 3 +5𝑥 2 +6𝑥 𝑥 2 +2𝑥 (𝑥)(𝑥+2)(𝑥+3) (𝑥)(𝑥+2)
7. (𝑥 4 −2𝑥 3 −5𝑥2 +6𝑥) = 𝑥 3 −4𝑥 2 +3𝑥 → 𝑥(𝑥−1)(𝑥+2)(𝑥−3) = 𝑥(𝑥−1)(𝑥−3) → 𝑥 2 + 3𝑥 = 𝑥 2 + 2𝑥, 𝑥 ≠ 0,1, −2,3
→ 𝑥 = 0, 𝑥 ≠ 0,1, −2,3, 𝑁𝑜 𝑝𝑜𝑠𝑠𝑖𝑏𝑙𝑒 𝑠𝑜𝑙𝑢𝑡𝑖𝑜𝑛

V. Complete the table then graph the following rational equation

Domain x-intercept y-intercept Asymptote/s


1 All reals except 0 No x-intercept No y-intercept x=0, y=0
1. 𝑦 = 𝑥
2 All reals except 0 No x-intercept No y-intercept x=0, y=0
2. 𝑦 = 𝑥
1 All reals except 0 -1 No y-intercept x=0, y=1
3. 𝑦 = 𝑥 + 1
1 All reals except -1 No x-intercept 1 x=-1, y=0
4. 𝑦 = 𝑥+1
1 All reals except -1 -2 2 x=-1, y=1
5. 𝑦 = 𝑥+1 + 1

VI. Solve the following problems


1. P = 2L + 2W → 30 = 2(2x+6) + 2(x-3) → 30 = 6x +6 →6x =24 → x = 4. Therefore, the dimension is
14m by 1m
2. A = bh/2 → ((3x-2)(2x+5))/2 = 136 → 6x2+11x-10 =272 → 6x2+11x-282 = 0 → (6x+47)(x-6) =0.
x= -47/6, x =6. The dimension of the triangle cannot be negative so x cannot be -47/6 so x=6.
3. Divide the triangle into 2 equal triangle and draw an altitude. The 2 triangles are 30-60-90 so the
altitudes measure will be (2x+6)(√3/2)=(x+3) √3. So the area is (2x+6)( (x+3) √3)/2 = (x2+6x+9) √3
4.Let x- be the time Carrot will be able to paint the house alone
1/6 is the part of the house Apple can finish in 1 hour while banana can finish 1/8 of the house. So
7 1 1 1
therefore 3/6+3/8+1/x = 1 → 8 + 𝑥 = 1 → 𝑥 = 8 → 𝑥 = 8. So therefore Carrot can paint the house in 8
hours
5. Let x be the time Arrf Arrf can create an application
then x+2 will be the time Meow Meow can create an application
Since they can finish creating an app in 10 hours therefore
1 1 1
→ + = → 10𝑥 + 20 + 10𝑥 = 𝑥 2 + 2𝑥, → 𝑥 2 − 18𝑥 − 20 = 0 → 𝑥 = 9 ± √101
𝑥 𝑥 + 2 10
by quadratic formula. But x cannot be negative so Arrf Arrf can create an application in 9 + √101 hours
and Meow meow can create an application in 11 + √101 hours

6. 3x - 8 + 2/x = 2x -1 → 2/x = -x +7 → 2= -x2 + 7x → x2-7x+2=0 → 𝑥 = (7 ± √41)/2


7.Let x be the speed going to the beach, then going back the speed is x-10
Distance Speed Time
To the beach 350 x 350/x
Going home 350 x-10 350/(x-10)

Note that it took 4 hours more going home than going to the beach. Therefore
350 350
− = 4 → 350𝑥 − 350(𝑥 − 10) = 4𝑥(𝑥 − 10) → 3500 = 4𝑥 2 − 40𝑥
𝑥 − 10 𝑥
→ 4𝑥 2 − 40𝑥 − 3500 = 0 → 𝑥 2 − 10𝑥 − 875 = 0 → (𝑥 − 35)(𝑥 + 25) = 0 → 𝑥 = 35, 𝑥 = −25
But the speed cannot be negative so x = 35 so it took him, 10 hours going to the beach and 14 hours
going back. So therefore the average speed is (350+350)/(14+10) = 700/24 =175/6 kph
8. Let x be the number of bihon ordered then.
Total amount Order Price per order
Bihon 180 x 180/x
Canton 60 30-x 60/(30-x)

Note that the price of bihon is twice the price of canton. Therefore
60 180 120 180
2( )= → = → 120𝑥 = 180(30 − 𝑥) → 2𝑥 = 3(30 − 𝑥) → 2𝑥 = 90 − 3𝑥
30 − 𝑥 𝑥 30 − 𝑥 𝑥
→ 5𝑥 = 90 → 𝑥 = 18. Therefore he ordered 18 Bihon and 12 Canton

Challenge.

1.(AD)(BC) = (BE)(AC). Therefore


𝐴𝐷(𝐵𝐶) (3𝑥+5)(𝑥+2)
BE = =
𝐴𝐶 𝑥−8

1 1 3
2. 1 = 2 → 𝑥+2 = 2 → 1 = 2𝑥 + 4 → 2𝑥 = −3 → 𝑥 = − 2.
𝑥+ 1
𝑥+ 1
𝑥+
𝑥+⋯

3. (f(2))(f(2))- 2(f(2))(g(2))+(g(2))(g(2)) = (f(2) – g(2))2 = (32) since f(x)-g(x)=3 for any x


therefore the answer is 9

Prepared by: RYAN S. ESTOLATAN, Kapitolyo High School